Gastroesophageal Reflux and Body Movement in Infants: Investigations with Combined Impedance-pH and Synchronized Video Recording - Tobias G. Wenzl; Olaf Stoltenburg; Jiri Silny; Heino Skopnik (Gastroenterology Research and Practice)
The aim of this paper was to investigate the temporal association of gastroesophageal reflux (GER) and body movement in infants. GER were registered by combined impedance-pH, documentation of body movement was done by video. Videorecording time (Vt) was divided into “resting time” and “movement time” and analyzed for occurrence of GER. Association was defined as movement 1 minute before/after the beginning of a GER. Statistical evaluation was by Fisher's exact test. In 15 infants, 341 GER were documented during Vt (86 hours). 336 GER (99%) were associated with movement, only 5 episodes (1%) occured during resting time. Movement was significantly associated with the occurrence of GER (𝑃<.0001). There is a strong temporal association between GER and body movement in infants. However, a clear distinction between cause and effect could not be made with the chosen study design. Combined impedance-pH has proven to be the ideal technique for this approach.